Outside Back Cover: Volume 1 Issue 2. Issue 2 (30th April 2022) - Unknown
Abstract : Outside Back Cover : The 'ball array' with the lose of balls means the existence of point vacancy defects on the photocatalyst. The colorful balls with the long tails represent the light driven generation of value‐added products like CH4 . The lightning indicates that solar light energy is converted into chemical energy over the deficient photocatalyst.